Artemisia dracunculus (Tarragon): A Review of Its Traditional Uses, Phytochemistry and Pharmacology - Ekiert, Halina; Świątkowska, Joanna; Knut, Ewa; Klin, Paweł; Rzepiela, Agnieszka; Tomczyk, Michał; Szopa, Agnieszka (Frontiers in Pharmacology, 2021)
Artemisia dracunculus L. (tarragon), Asteraceae, is a species that has long been used in traditional Asian medicine, mainly in Iran, Pakistan, Azerbaijan and India. It is known as a spice species in Asia, Europe and the Americas. The raw materials obtained from this species are herb and leaf. The presence of essential oil with a highly variable composition, as well as flavonoids, phenolic acids, coumarins and alkamides, determines the medicinal and/or spice properties of the plant. In traditional Asian medicine, this species is used, for example, in the treatment of digestive system diseases as an analgesic, hypnotic, antiepileptic, anti-inflammatory and antipyretic agent, and as an effective remedy in the treatment of helminthiasis. Nowadays, A. dracunculus is the subject of professional phytochemical and pharmacological research. Pharmacological studies have confirmed its anti-inflammatory and analgesic effects known from traditional uses; they have also proved very important new findings regarding its biological activity, such as antioxidant, immunomodulating and anti-tumour activities, as well as hepatoprotective and hypoglycaemic effects. A. dracunculus has long-held an established position in the food industry as a spice. And its use is growing in the cosmetics industry. Moreover, it is the subject of biotechnological research focused mainly on the development of micro-propagation protocols.